The Influence of Service Quality, Product Quality, and Price Perception on Customer Satisfaction at Shanum Florist Fresh Flower Shop in Tuban City - Dessy Anggelina Tiarakasih; Supriyono Supriyono; Nanik Hariyana (Digital Innovation : International Journal of Management, 2025)
The ornamental flower industry in Indonesia has shown a significant growth trend and is increasingly gaining popularity among the public. Numerous flower shops have emerged in various cities, offering a wide range of cut flowers. This sector holds promising potential for continuous development. Cut flowers of various types also possess high economic value, making them an attractive and profitable business opportunity. This study aims to examine the influence of service quality, product quality, and price perception on customer satisfaction at Shanum Florist Fresh Flower Shop in Tuban City. This study employed a quantitative research approach using a survey method by distributing online questionnaires to respondents selected through a convenience sampling technique, involving a total of 112 participants. The collected data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of the SmartPLS software. The study results reveal that service quality positively and significantly influences customer satisfaction, while product quality shows a positive yet insignificant impact. Additionally, price perception demonstrates a positive and significant relationship with customer satisfaction.